Studies on the ontogenic radio-sensitivity in Callosobruchus species complex to establish a generic dose of phytosanitary irradiation as a post harvest quarantine treatment for disinfestation of pulses. (June 2020) - Seth, R.K.; Patil, B.V.; Zarin, Mahtab; Khan, Zubeda; Hanchinal, S.G.; Haveri, Rachappa V.; Gopalkrishna, Akshatha; Seth, Ranjana
Abstract: The effects of gamma radiation were observed on the metamorphosis and reproduction as key target features to be intercepted for disinfestation of the three major pest bruchid species, Callosobruchus maculatus (Fabricius), C. analis (Fabricius) and C. chinensis (Linnaeus) irradiated in the various ontogenic stages. The present study was aimed to determine an efficacious generic dose of phytosanitary irradiation (PI) for bruchid disinfestation in pulses. Callosobruchus chinensis was the most radio-resistant species among the present tested species, and male bruchids were more radio-resistant than the females in this species complex. In this complex of tested bruchid species, the gamma dose required to cause 100% metamorphic disruption in the most radio-resistant pre-imaginal stage (pharate adult) was 20–46% higher than the dose required to induce complete sterility in the most radio-resistant imaginal stage (4–5 day old). The effective dose inducing 99.9% impact (ED99.9 ) was 105 Gy for sterility induction but 181 Gy to induce metamorphic disruption in the most radio-resistant pre-imaginal pharate adult in C. chinensis, whereas the most radio-resistant imaginal stage (4–5 day old adult) of this species required 124 Gy for complete sterilization. Based on these results, 160–200 Gy as phytosanitary irradiation dose range was evaluated on a semi-large scale testing on the pigeonpea pulse seeds having mixed infestation of Callosobruchus species complex, which indicated that 200 Gy might be considered as a feasible generic dose of phytosanitary irradiation for bruchid disinfestation in pulses. Highlights: Metamorphic disruption was positively correlated with irradiation in the bruchids. Pharate adult was the most radio-resistant ontogenic stage to check metamorphosis. 100% ovipositional check was possible by using 352 Gy for bruchid species complex. Egg infertility in the bruchid species complex could be achieved at 124 Gy. A generic dose of 200 Gy might be established for quarantine treatment of bruchids.